Speaker variability in the realisation of lexical tones. (17th October 2016) - Chan, Ricky
Abstract : While previous studies on the speaker-discriminatory power of static f0 parameters abound, few have focused on the dynamic and linguistically structured aspects of f0. Lexical tone offers a case in point for this endeavour. This article reports an exploratory study on the speaker-discriminatory power of individual lexical tones and of the height relationship of level tone pairs in Cantonese, and the effects of voice level and linguistic condition on their realisation. Twenty native Cantonese speakers produced systematically controlled words either in isolation or in a carrier sentence under two voice levels (normal and loud). Results show that f0 height and f0 dynamics are separate dimensions of a tone and are affected by voice level and linguistic condition in different ways. Moreover, discriminant analyses reveal that the contours of individual tones and the height differences of level tone pairs are useful parameters for characterising speakers.